Teamwork Competence in Journalism Education: Evidence From TV Organizations’ News Team in Taiwan - Wang, Cheng-Hui; Liu, Gloria Hui-Wen; Yen, Chia-Dai (Frontiers in Psychology, 2022)
The rapid development of digital technologies has transformed the world but can be a double-edged sword. We study the interaction of important variables that affect individual news reporters' performance in which digital technology is the dominant feature. A multi-level model illustrates how transactive memory and job competence affect individual performance. The empirical study includes data from 19 teams of news reporters and 211 valid survey responses, applying hierarchical linear modeling to analyze the data. The results indicate that transactive memory and technology competence help to improve a reporter’s job performance. More importantly, teamwork competence fully mediates the relationships. Our findings thus suggest that teamwork competence is the core skill. Neither technology competence nor transactive memory alone translates directly into enhanced individual performance.